Robotic multiquadrant colorectal procedures: A single-center experience and a systematic review of the literature - Bianchi, Giorgio; Gavriilidis, Paschalis; Martínez-Pérez, Aleix; de’Angelis, Gian Luigi; Uzzan, Mathieu; Sobhani, Iradj; Coccolini, Federico; Schena, Carlo Alberto; Carra, Maria Clotilde; Spinoglio, Giuseppe; de’Angelis, Nicola (Frontiers in Surgery, 2022)
Purpose: Robotic surgery has been progressively implemented for colorectal procedures but is still limited for multiquadrant abdominal resections. The present study aims to describe our experience in robotic multiquadrant colorectal surgeries and provide a systematic review and meta-analysis of the literature investigating the outcomes of robotic total proctocolectomy (TPC), total colectomy (TC), subtotal colectomy (STC), or completion proctectomy (CP) compared to laparoscopy. Methods: At our institution 16 consecutive patients underwent a 2- or 3-stage totally robotic total proctocolectomy (TPC) with ileal pouch-anal anastomosis. A systematic review of the literature was performed to select studies on robotic and laparoscopic multiquadrant colorectal procedures. Meta-analyses were used to compare the two approaches. Results: In our case series, 14/16 patients underwent a 2-stage robotic TPC for ulcerative colitis with a mean operative time of 271.42 (SD:37.95) minutes. No conversion occurred. Two patients developed postoperative complications. The mean hospital stay was 8.28 (SD:1.47) days with no readmissions. Mortality was nil. All patients underwent loop-ileostomy closure, and functional outcomes were satisfactory. The literature appraisal was based on 23 retrospective studies, including 736 robotic and 9904 laparoscopic multiquadrant surgeries. In the robotic group, 36 patients underwent STC, 371 TC, 166 TPC, and 163 CP. Pooled data analysis showed that robotic TC and STC had a lower conversion rate (OR=0.17;95%CI:0.04-0.82; p=0.03) than laparoscopic TC and STC. The robotic approach was associated with longer operative time for TC and STC (MD=104.64;95%CI:18.42-190.87; p=0.02) and TPC and CP (MD=38.8;95%CI:18.7-59.06; p= 0.0002), with no differences for postoperative complications and hospital stay. Reports on urological outcomes, sexual dysfunction, and quality of life were missing. Conclusions: Our experience and the literature suggest that robotic multiquadrant colorectal surgery is safe and effective, with low morbidity and mortality rates. Nevertheless, the overall level of evidence is low, and functional outcomes of robotic approach remain largely unknown.